A porous transport layer for a proton exchange membrane water electrolyser and methods of making and using the same

CN122522276BActive Publication Date: 2026-10-16DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611009118.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-16
Estimated Expiration
2046-07-08

AI Technical Summary

Technical Problem

[0004]本发明针对现有质子交换膜水电解多孔传输层表面改性涂层存在的贵金属用量高、界面接触电阻大、涂层附着力差且长期服役稳定性不足等问题,提供一种用于质子交换膜水电解的多孔传输层及其制备方法

Benefits of technology

1、本发明提供一种多孔传输层,包括钛基体和从基体向外依次层叠设置的Ta阻隔层、PtTa过渡层、Pt表面导电层。其中Ta阻隔层紧密贴合基体,有效隔绝强酸性电解环境对基体的腐蚀,同时抑制基体中的金属元素向涂层表面迁移,从根源上避免钛基PTL表面钝化膜的形成。在Ta阻隔层与Pt表面导电层之间设置至少三层Pt质量含量呈梯度变化的PtTa复合过渡层,能够构建更连续、稳定的电子传输通道,有效降低因基体钝化层形成导致的电阻上升问题,同时使层间成分变化梯度更平缓,显著降低相邻层间的电偶腐蚀驱动力,最大程度避免界面电位差突变导致的局部强腐蚀问题,若层数低于三层,则电位差梯度降低不明显,对电偶腐蚀的抑制效果不足;通过保持各子层Pt的面载量相同且仅线性降低Ta面载量,能有效简化工艺参数、减少操作变量以保证生产一致性;且合金化的PtTa过渡层缓解了涂层间因成分突变带来的内应力与界面剥离问题,显著增强涂层与基体、各涂层之间的界面附着力,防止涂层脱落。Pt表面导电层作为复合涂层的最外层,可进一步抑制涂层表面的氧化反应,同时保证PTL与催化剂层之间的低接触电阻,维持PTL优异的导电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122522276B_ABST
    Figure CN122522276B_ABST
Patent Text Reader

Abstract

The present application relates to hydrogen energy preparation technical field, specifically relates to a kind of porous transport layer for proton exchange membrane water electrolysis cell and its preparation method and application.The porous transport layer includes titanium matrix and composite coating, the composite coating includes Ta barrier layer, PtTa transition layer and Pt surface conductive layer in turn from matrix to outside.The present application adopts magnetron sputtering process to prepare the composite coating, with the characteristics of process parameter precision controllable, batch preparation repeatability excellent, can be widely applied to the surface modification of porous transport layer in proton exchange membrane water electrolysis device, effectively improve the overall performance and service life of electrolyzer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hydrogen energy production technology, specifically to the field of proton exchange membrane water electrolysis technology, and more specifically, to a porous transport layer for a proton exchange membrane water electrolysis cell, its preparation method, and its application. Background Technology

[0002] Proton exchange membrane electrolysis (PEMWE) technology has become one of the core technologies in the field of green hydrogen production due to its significant advantages such as compact structure, fast dynamic response speed, high operating current density, and strong adaptability to operating conditions. It is also an important hydrogen production technology path for the future industrialization of hydrogen energy. However, in the actual operation of a proton exchange membrane electrolyzer, the anode side is always under harsh conditions of high potential, strong acidity, and high temperature. A titanium dioxide passivation film will spontaneously form on the titanium surface of the titanium-based porous transport layer (PTL). This passivation film has extremely poor conductivity, which will cause a sharp increase in the interfacial contact resistance (ICR) between the PTL and the catalyst layer. This will lead to a significant increase in the energy consumption of the electrolysis system, and at the same time, the overall performance of the electrolyzer will rapidly decline, which seriously restricts the industrial application of PEMWE technology.

[0003] To address the technical challenge of passivation on titanium-based PTL surfaces, the mainstream solution in the industry is to deposit noble metal coatings (such as gold, iridium, and platinum) on the titanium felt substrate. These coatings utilize the stable chemical properties of noble metals to construct a durable and highly conductive protective layer on the PTL surface. For example, Chinese patent CN120465070A discloses a technique for depositing a pure platinum coating on a titanium felt surface. While this method effectively ensures the conductivity of the PTL, it suffers from excessive platinum loading, leading to high PTL manufacturing costs. Furthermore, the pure platinum coating exhibits poor interfacial adhesion to the titanium felt substrate, making it prone to peeling off under long-term, harsh operating conditions, severely impacting the electrolyzer's lifespan and performance stability. To reduce costs, researchers have attempted to modify the surface of titanium-based PTLs using non-noble metal niobium coatings (e.g., Chinese patent CN121472891A). However, such coatings are prone to oxidation at high potentials, forming a high-resistivity oxide layer, causing a sharp increase in ICR (intercalation resistance), and the long-term service stability of the coating fails to meet practical application requirements. Summary of the Invention

[0004] This invention addresses the problems of existing surface-modified coatings for porous transport layers in proton exchange membrane (PTT) water electrolysis, such as high precious metal content, high interfacial contact resistance, poor coating adhesion, and insufficient long-term service stability. It provides a porous transport layer for PTT water electrolysis and its preparation method. By constructing a functionalized multilayer composite structure on the surface of a titanium-based substrate, the amount of precious metal Pt is reduced while effectively suppressing the high contact resistance caused by the substrate passivation film. This achieves a synergistic improvement in low interfacial contact resistance and high corrosion resistance, while also considering the high conductivity, strong corrosion resistance, and long-term stability of the PTL.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: The first aspect of this invention provides a porous transport layer for a proton exchange membrane water electrolyzer, the porous transport layer comprising a titanium substrate and a composite coating, the composite coating comprising, from the substrate outwards: Ta barrier layer, wherein the Ta barrier layer is in contact with the substrate; The PtTa transition layer comprises at least three sub-layers, with the mass content of Pt increasing progressively from the side closest to the substrate toward the surface of the composite coating. Pt surface conductive layer.

[0006] In the above technical solution, the total areal load of Pt in the composite coating is further described as 0.04~0.1 mg / cm³. -2 .

[0007] The surface load mentioned in this article refers to the mass of the corresponding metal or alloy loaded per unit geometric area. The test method uses inductively coupled plasma optical emission spectrometry (ICP-OES), and the unit is mg / cm³. -2 .

[0008] In the above technical solution, the thickness of the Pt surface conductive layer is ≥30nm.

[0009] In the above technical solution, further, in the PtTa transition layer, the mass fraction of Pt in the first sub-layer is 3%~8%, and the mass fraction of Pt in the last sub-layer is 20%~40%.

[0010] A second aspect of the present invention provides a method for preparing the above-mentioned porous transport layer, comprising the following steps: (1) Matrix pretreatment: The titanium matrix is ​​pretreated; (2) Substrate loading and plasma cleaning: The pretreated titanium substrate is placed in the magnetron sputtering coating chamber, and after vacuuming, argon gas is introduced to perform sputter cleaning on the surface of the titanium substrate under negative bias. (3) Deposition of Ta barrier layer: Using a Ta target as the sputtering source, a Ta barrier layer is deposited on the substrate surface under an argon atmosphere and a negative bias voltage on the substrate. (4) Deposit PtTa transition layer: Using Ta target and Pt target as sputtering sources, under argon atmosphere and substrate negative bias, keep the working power of Pt target constant to ensure that the surface load of Pt in each sub-layer is the same. By adjusting the working current of Ta target to gradually decrease, each sub-layer is deposited sequentially on the surface of Ta barrier layer to form PtTa transition layer; (5) Deposit Pt surface conductive layer: Turn off Ta target, use Pt target as sputtering source, under argon atmosphere and substrate negative bias, deposit Pt surface conductive layer on the surface of PtTa transition layer; (6) Cooling and removing the part: After the deposition process is completed, the part is naturally cooled to room temperature under an argon atmosphere to obtain the porous transport layer.

[0011] In the above technical solution, further, in step (1), the pretreatment includes water washing-degreasing-water washing-drying, wherein the degreasing agent used for degreasing is a mixture of anhydrous ethanol and acetone.

[0012] In the above technical solution, further, in step (2), the bias voltage of the sputtering cleaning is -600~-1000 V, and the sputtering cleaning time is 10 min~2 h.

[0013] In the above technical solution, further, in step (3), the parameters of the deposited Ta barrier layer are: the working current of the Ta target is 500~4000 mA, the substrate bias voltage is -50~-300 V, and the working pressure of the magnetron sputtering coating chamber is 0.1~1 Pa.

[0014] In the above technical solution, further, in step (4), the deposition parameters of the PtTa transition layer are as follows: during the deposition of each sublayer, the working power of the Pt target is 30~200 W, and the working current of the Ta target decreases layer by layer from the first sublayer to the last sublayer; during the entire deposition process, the working current of the Ta target is 900~2500 mA, the substrate bias voltage is -50~-300 V, and the working pressure of the magnetron sputtering coating chamber is 0.1~1 Pa.

[0015] In the above technical solution, further, in step (5), the parameters of the Pt surface conductive layer are: the working power of the Pt target is 50~250 W, the substrate bias voltage during deposition is -50~-300 V, and the working pressure of the magnetron sputtering coating chamber is 0.1~1 Pa.

[0016] In the above technical solution, further, in steps (2) to (5), the substrate temperature is controlled at 80~200 °C.

[0017] A third aspect of the present invention provides an application of the above-mentioned porous transport layer as an anode porous transport layer in a proton exchange membrane water electrolyzer.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention provides a porous transport layer, comprising a titanium substrate and a Ta barrier layer, a PtTa transition layer, and a Pt surface conductive layer, which are sequentially stacked from the substrate outwards. The Ta barrier layer is tightly bonded to the substrate, effectively isolating it from corrosion by the strongly acidic electrolytic environment, while simultaneously inhibiting the migration of metal elements from the substrate to the coating surface, thus preventing the formation of a passivation film on the titanium-based PTL surface at its source. By setting at least three PtTa composite transition layers with gradient Pt mass content between the Ta barrier layer and the Pt surface conductive layer, a more continuous and stable electron transport channel can be constructed, effectively reducing the resistance increase caused by the formation of the substrate passivation layer. Simultaneously, the compositional gradient between layers is smoother, significantly reducing the driving force of galvanic corrosion between adjacent layers and minimizing localized severe corrosion caused by abrupt changes in interface potential difference. If the number of layers is less than three, the reduction in potential gradient is not significant, resulting in insufficient suppression of galvanic corrosion. By maintaining the same Pt ​​areal loading in each sublayer and only linearly reducing the Ta areal loading, process parameters can be effectively simplified, and operational variables reduced to ensure production consistency. Furthermore, the alloyed PtTa transition layer alleviates the internal stress and interface delamination problems caused by abrupt changes in composition between coatings, significantly enhancing the interfacial adhesion between the coating and the substrate, and between different coating layers, preventing coating detachment. As the outermost layer of the composite coating, the Pt surface conductive layer further inhibits the oxidation reaction on the coating surface while ensuring low contact resistance between the PTL and the catalyst layer, maintaining the excellent conductivity of the PTL.

[0019] 2. This invention controls the thickness of the surface Pt conductive layer to resist the erosion of the anode side by bubbles and weaken the effect of high-potential oxidation corrosion. This avoids the defects of ultra-thin Pt layers being easily penetrated and unable to provide long-term protection for the underlying structure. While maintaining a low Pt loading, it ensures the structural integrity and performance stability of the coating under high-potential and strong erosion environment.

[0020] 3. In the composite coating of the porous transport layer of this invention, most of the volume is borne by the inexpensive Ta barrier layer, effectively reducing the amount of precious metal Pt used and lowering the Pt areal loading to 0.1 mg / cm³. -2 The cost is significantly lower than that of traditional pure Pt coatings, effectively reducing the preparation cost of titanium-based PTL.

[0021] 4. The porous transport layer of this invention is prepared using a standard magnetron sputtering process, which allows for precise control of various parameters. The resulting coating is uniform and dense, exhibits excellent adhesion to the substrate, and has good batch repeatability, making it suitable for large-scale industrial production. The process of multi-layer gradient structure can be achieved through multi-target co-sputtering or power regulation without additional complex procedures, thus balancing performance improvement and industrial feasibility. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the porous transport layer of the present invention; Figure 2 These are comparison images of the contact angle tests of the porous transport layers prepared in Examples 1-2 and Comparative Examples 1-5. Figure 3 Comparison of the total areal load of Pt in the porous transport layers prepared in Examples 1-2 and Comparative Examples 1-5; Figure 4 Comparison of interfacial contact resistance of porous transport layers prepared in Examples 1-2 and Comparative Examples 1-5 before corrosion testing; Figure 5 Comparison of interfacial contact resistance of porous transport layers prepared in Examples 1-2 and Comparative Examples 1-2 after corrosion testing; Figure 6 The porous transport layers prepared for Examples 1-2 and Comparative Examples 1-5 were at 4 mA cm⁻¹ -2 Comparison of accelerated life test curves under different conditions; Figure 7 The chart shows a comparison of the durability tests for Application Example 1 and Application Example 2. Detailed Implementation

[0023] The present invention will be further illustrated by specific implementation examples below, but the present invention is not limited to the following embodiments.

[0024] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained commercially or prepared according to conventional methods known to those skilled in the art.

[0025] Example 1 Preparation steps: (1) Substrate pretreatment: Immerse the titanium felt (5cm×5cm×0.4mm) substrate in deionized water and ultrasonically clean for 10-15 minutes to remove surface dust and loose impurities. Then immerse it in a mixture of anhydrous ethanol and acetone and ultrasonically clean for 10-15 minutes to remove surface oil. Then immerse it in deionized water and ultrasonically clean for 10-15 minutes to remove dissolved impurities and organic matter. After that, let it air dry naturally. (2) Substrate loading and plasma cleaning: The titanium felt is placed in the magnetron sputtering coating chamber and the vacuum is evacuated to 3.6 × 10⁻⁶. -3 Pa, introduce argon gas to a pressure of 2 Pa, apply a bias voltage of -700 V, and clean the substrate surface for 20 minutes; (3) Deposition of Ta barrier layer: Adjust the argon pressure to 0.5 Pa, turn on the Ta target, use 1200 mA current, and deposit for 15 minutes at a substrate bias voltage of -50 V and a temperature of 100 °C to form Ta barrier layer; (4) Deposition of PtTa transition layer: Maintaining argon pressure of 0.5 Pa and substrate temperature of 100℃, simultaneously turn on the Ta target and Pt target, bias voltage of -50 V, and constant working power of Pt target of 50 W. From the Ta barrier layer to the surface of the composite coating, the working current of the Ta target for the first sublayer is 1500 mA, the working current of the Ta target for the second sublayer is 1200 mA, and the working current of the Ta target for the third sublayer is 900 mA. Each sublayer is deposited for 2 minutes, so that the mass content of Pt in each sublayer increases layer by layer, with the first sublayer being 7.51%, the second sublayer being 11.02%, and the third sublayer being 20.63%, forming a PtTa transition layer. The areal loading of Pt in each sublayer is 0.0013 mg cm⁻¹. -2 ; (5) Deposition of Pt surface conductive layer: turn off Ta target, turn on only Pt target, power 100 W, maintain argon pressure 0.5 Pa, substrate temperature 100℃, bias voltage -50 V, deposit for 17 minutes to form Pt surface conductive layer. The thickness of its surface Pt conductive layer is calculated to be about 30 nm. (6) Cooling and taking out the sample: After all the deposition processes are completed, keep the argon atmosphere in the coating chamber and let it cool naturally to room temperature before taking out the sample to obtain a porous transport layer with a composite coating.

[0026] Figure 1 This is a schematic diagram of the porous transport layer prepared in Example 1.

[0027] The effect on hydrophobicity was determined by contact angle testing, and the results are as follows: Figure 2 As shown, the contact angle of Example 1 is 139.9°, indicating that the coating has the best hydrophobicity.

[0028] The Pt areal load of the porous transport layer prepared in Example 1 was tested by ICP-OES, and the results are as follows: Figure 3 In Example 1, the total areal load of Pt was only 0.045 mg cm⁻¹. -2 This significantly reduced costs.

[0029] The porous transport layer prepared in Example 1 was subjected to an initial conductivity test, and the results are as follows: Figure 4 As shown, in Example 1, the interfacial contact resistance at 1.5 MPa before corrosion was only 2.1 mΩ cm. 2 The result was lower than that of the commercially available pure platinum-titanium plating felt in Comparative Example 2. The sample was subjected to a 4 A cm test in a sulfuric acid solution at 80 °C and pH = 0.5. -2 Conductivity was evaluated in Example 1 after accelerated corrosion testing, and the results are as follows: Figure 5 As shown, in Example 1, the interfacial contact resistance after corrosion at 1.5 MPa was only 6.3 mΩ cm. 2 .

[0030] The porous transport layer prepared in Example 1 was subjected to accelerated lifetime testing by applying 4 A cm⁻¹ of sulfuric acid solution at pH = 0.5 at 80 °C. -2 Current, the result is as follows Figure 6 As shown, its lifespan is 10.6 h, which significantly exceeds that of the commercially available pure platinum-plated titanium felt in Comparative Example 2, and also exceeds that of the Comparative Example 1 sample with the same Pt ​​surface load.

[0031] Example 2 The preparation steps are the same as in Example 1, except that in step (4), the working current of the Ta target in the first sublayer is 2500 mA, the working current of the Ta target in the second sublayer is 1500 mA, and the working current of the Ta target in the third sublayer is 500 mA. Each sublayer is deposited for 2 minutes, so that the mass content of Pt in each sublayer increases layer by layer, with the first sublayer having 4.22% and the last sublayer having 38.3%, forming a PtTa transition layer; the other conditions are the same as in Example 1. Hydrophobicity testing was performed on Example 2 using the same method as Example 1, with a contact angle of 135.2°. The Pt areal loading was also tested on Example 2 using the same method as Example 1, with a total Pt areal loading of 0.044 mg / cm². -2 The conductivity of Example 2 before corrosion was tested using the same method as in Example 1, and the results are as follows. Figure 4 The interfacial contact resistance at 1.5 MPa is 2.49 mΩ cm. 2 The conductivity of Example 2 after corrosion was evaluated using the same method as in Example 1, and the results are as follows. Figure 5 The interfacial contact resistance at 1.5 MPa is 7.60 mΩ cm. 2 Accelerated life testing was performed on Example 2 using the same method as in Example 1, and the results are as follows. Figure 6 Its lifespan is 8.28 hours.

[0032] Comparative Example 1 The preparation steps are the same as in Example 1, except that step (4) is omitted, the deposition time in step (3) is 17 min, the deposition time in step (5) is 18 min, and the other conditions are the same as in Example 1.

[0033] Hydrophobicity testing was performed on Comparative Example 1 using the same method as in Example 1, with a contact angle of 128.8°. The Pt areal loading of Comparative Example 1 was also tested using the same method as in Example 1, with a total Pt areal loading of 0.044 mg / cm². -2 The conductivity of Comparative Example 1 before corrosion was tested using the same method as in Example 1, and the results are as follows. Figure 4 The interfacial contact resistance is 2.5 mΩ cm at 1.5 MPa. 2 The conductivity of Comparative Example 1 after corrosion was evaluated using the same method as in Example 1, and the results are as follows. Figure 5The interfacial contact resistance is 20.5 mΩcm at 1.5 MPa. 2 Accelerated life testing was performed on Comparative Example 1 using the same method as in Example 1, and the results are as follows. Figure 6 Its lifespan is 6.8 hours.

[0034] Comparative Example 2 It is a Bekaert commercial Pt-plated titanium felt, model PTL Ti-56 / 250 PT200.

[0035] Hydrophobicity testing was performed on Comparative Example 2 using the same method as in Example 1, and the contact angle of Comparative Example 2 was 124.2°. The Pt areal loading capacity testing was also performed on Comparative Example 2 using the same method as in Example 1, and the results are as follows: Figure 3 The total areal loading of Pt is 0.261 mg / cm³. -2 The conductivity of Comparative Example 2 before corrosion was tested using the same method as in Example 1, and the results are as follows. Figure 4 The interfacial contact resistance is 5.5 mΩcm at 1.5 MPa. 2 The conductivity of Comparative Example 2 after corrosion was evaluated using the same method as in Example 1, and the results are as follows. Figure 5 The interfacial contact resistance at 1.5 MPa is 29.8 mΩ cm. 2 Accelerated life testing was performed on Comparative Example 2 using the same method as in Example 1, and the results are as follows. Figure 6 Its lifespan is 2.7 hours.

[0036] Comparative Example 3 The preparation steps are the same as in Example 1, except that in step (3), the deposition power is changed to 1500mA and the deposition time is changed to 30min; in step (4), a single layer of PtTa is deposited, the Pt target deposition power is the same as in Example 1, the Ta target deposition power is changed to 1500mA and the deposition time is changed to 3min; in step (5), the deposition time is 3min and the thickness of the surface Pt conductive layer is about 5 nm.

[0037] Hydrophobicity was tested on Comparative Example 3 using the same method as in Example 1, and the contact angle of Comparative Example 3 was 129.2°. The Pt areal loading was tested on Comparative Example 3 using the same method as in Example 1, and the total Pt areal loading was 0.012 mg / cm³. -2 The conductivity of Comparative Example 3 before corrosion was tested using the same method as in Example 1, and the results are as follows. Figure 4 The interfacial contact resistance at 1.5 MPa is 2.21 mΩ cm. 2 Because its lifespan was too short to be compared, its conductivity after corrosion was not evaluated. Accelerated lifetime testing was performed on Comparative Example 3 using the same method as Example 1, and the results are as follows. Figure 6 Its lifespan is 0.62 hours.

[0038] Comparative Example 4 The preparation steps are the same as in Example 1, except that in step (4), the Pt target deposition power is changed to 100W and the deposition time of each sublayer is changed to 4min; in step (5), the deposition time is changed to 4min.

[0039] Hydrophobicity was tested on Comparative Example 4 using the same method as in Example 1, and the contact angle of Comparative Example 4 was 135.2°. The Pt areal loading was tested on Comparative Example 4 using the same method as in Example 1, and the Pt areal loading was 0.044 mg / cm². -2 The conductivity of Comparative Example 4 before corrosion was tested using the same method as in Example 1, and the results are as follows. Figure 4 The interfacial contact resistance is 2.4 mΩ cm at 1.5 MPa. 2 Because its lifespan was too short to be compared, its conductivity after corrosion was not evaluated. Accelerated lifetime testing was performed on Comparative Example 4 using the same method as Example 1, and the results are as follows. Figure 6 Its lifetime is 0.71 h, and its surface Pt thickness is calculated to be approximately 5 nm.

[0040] Comparative Example 5 The preparation steps are the same as in Example 1, except that in step (4), a single layer of PtTa is deposited. The Pt target deposition power is the same as in Example 1, the Ta target deposition power is 1200mA, the deposition time is 2min, and the other conditions are the same as in Example 1.

[0041] Hydrophobicity was tested in Comparative Example 5 using the same method as in Example 1. The contact angle of Comparative Example 3 was 130.7°. The areal loading of Pt in Comparative Example 5 was tested using the same method as in Example 1. The areal loading of Pt was 0.0531 mg / cm³. -2 Accelerated life testing was performed on Comparative Example 5 using the same method as in Example 1, and the results are as follows. Figure 6 Its lifespan is 6.40 hours.

[0042] In summary, compared with Comparative Examples 1 and 5, Examples 1 and 2 achieved a comprehensive performance improvement through structural optimization without changing the Pt loading. The single-layer structures of Comparative Examples 1 and 5, due to abrupt changes in composition, suffer from high interlayer galvanic corrosion driving force and large interfacial internal stress, leading to easy peeling. In contrast, the gradient design of Examples 1 and 2 not only reduces the risk of galvanic corrosion but also effectively alleviates internal stress through the compositionally gradual interface, significantly enhancing coating adhesion.

[0043] Compared to the 5 nm ultrathin Pt surface conductive layer in Comparative Examples 3 and 4, Examples 1 and 2 used a 30 nm thick continuous Pt surface conductive layer. The ultrathin Pt surface conductive layer is easily consumed quickly, leading to exposure of the underlying Ta layer, which causes substrate corrosion and increased contact resistance; while the thicker continuous Pt layer significantly improves the protection of the underlying structure and avoids substrate corrosion problems.

[0044] At 4 A cm -2 In accelerated lifetime testing at high current density, Example 1 exhibited a lifetime of approximately 10.6 hours, significantly exceeding that of all comparative examples 1-5. In a simulated PEMWE anodic environment (80°C, pH=0.5 H2SO4), after 4A cm⁻¹... -2 After 2 hours of accelerated corrosion at high current density, the interfacial contact resistance (ICR@1.5 MPa) between the coating and the carbon paper remained as low as approximately 6.3 mΩ cm. 2 The total surface loading of Pt is only 0.045 mg / cm³. -2 Compared to the commercial sample in Comparative Example 2, the cost was significantly reduced, demonstrating its excellent practical durability and economy.

[0045] Application Example 1 According to the preparation method of Example 1, with an effective area of ​​4 cm² 2 A composite coating with a thickness of 0.4 nm and a porosity of 75% was prepared on a titanium felt to obtain a porous transport layer. This porous transport layer was then assembled with a membrane electrode to form a complete PEMWE. The membrane electrode used was Nafion 115, and the cathode was loaded with 50 wt% Pt / C as a hydrogen evolution catalyst at a loading of 0.4 mg / cm³. -2 The anode-supported iridium black catalyst (Tanaka Precious Metals, Japan) has a loading of 1 mg cm⁻¹. -2 .

[0046] At 1500 mA cm 2 The durability test under the conditions of 1000 h yielded the following results: Figure 7 As shown, the electrolysis potential is maintained at 1.77V.

[0047] Application Example 2 The commercial Pt-coated titanium felt of Comparative Example 2 was assembled with the membrane electrode to form a complete PEMWE. The membrane electrode was used in the same way as in Application Example 1.

[0048] At 1500 mA cm 2 The durability test under the conditions of 1000 h yielded the following results: Figure 7 As shown, the electrolysis potential is maintained at 1.84V.

[0049] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the implementation. The scope of protection of the present invention should be determined by the scope defined in the claims. Other variations or modifications can be made based on the above description. Obvious variations or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A porous transport layer for proton exchange membrane water electrolysis, characterized in that, The porous transport layer comprises a titanium substrate and a composite coating, wherein the composite coating comprises, from the substrate outwards, the following: Ta barrier layer, wherein the Ta barrier layer is in contact with the substrate; The PtTa transition layer comprises at least three sublayers, arranged from the side closest to the substrate toward the surface of the composite coating, wherein the mass content of Pt in each sublayer increases progressively. In the PtTa transition layer, the mass fraction of Pt in the first sublayer is 3% to 8%, and the mass fraction of Pt in the last sublayer is 20% to 40%. A Pt surface conductive layer, wherein the thickness of the Pt surface conductive layer is ≥30nm; In the composite coating, the total areal loading of Pt is 0.04~0.1 mg / cm³. -2 .

2. A method for preparing the porous transport layer according to claim 1, characterized in that, Includes the following steps: (1) Matrix pretreatment: The titanium matrix is ​​pretreated; (2) Substrate loading and plasma cleaning: The pretreated titanium substrate is placed in the magnetron sputtering coating chamber, and after vacuuming, argon gas is introduced to perform sputter cleaning on the surface of the titanium substrate under negative bias. (3) Deposition of Ta barrier layer: Using a Ta target as the sputtering source, a Ta barrier layer is deposited on the substrate surface under an argon atmosphere and a negative bias voltage on the substrate. (4) Deposition of PtTa transition layer: Using Ta target and Pt target as sputtering source, under argon atmosphere and negative bias of substrate, keep the working power of Pt target constant to ensure that the surface load of Pt in each sublayer is the same. By adjusting the working current of Ta target to gradually decrease, each sublayer is deposited sequentially on the surface of Ta barrier layer to form PtTa transition layer. (5) Deposit Pt surface conductive layer: Turn off the Ta target, use the Pt target as the sputtering source, and deposit a Pt surface conductive layer on the surface of the PtTa transition layer under argon atmosphere and substrate negative bias conditions. (6) Cooling and removing the part: After the deposition process is completed, the part is naturally cooled to room temperature under an argon atmosphere to obtain the porous transport layer.

3. The preparation method according to claim 2, characterized in that, In step (1), the pretreatment includes water washing-degreasing-water washing-drying, wherein the degreasing agent used for degreasing is a mixture of anhydrous ethanol and acetone.

4. The preparation method according to claim 2, characterized in that, In step (2), the bias voltage for sputter cleaning is -600~-1000 V, and the sputter cleaning time is 10 min~2 h.

5. The preparation method according to claim 2, characterized in that, In step (3), the parameters for depositing the Ta barrier layer are: the working current of the Ta target is 500~4000 mA, the substrate bias voltage is -50~-300 V, and the working pressure of the magnetron sputtering coating chamber is 0.1~1 Pa.

6. The preparation method according to claim 2, characterized in that, In step (4), the deposition parameters for the PtTa transition layer are as follows: during the deposition of each sublayer, the working power of the Pt target is 30~200 W, and the working current of the Ta target decreases layer by layer from the first sublayer to the last sublayer; during the entire deposition process, the working current of the Ta target is 900~2500 mA, the substrate bias voltage is -50~-300 V, and the working pressure of the magnetron sputtering coating chamber is 0.1~1 Pa.

7. The preparation method according to claim 2, characterized in that, In step (5), the parameters of the Pt surface conductive layer are: the working power of the Pt target is 50~250 W, the substrate bias voltage is -50~-300 V, and the working pressure of the magnetron sputtering coating chamber is 0.1~1 Pa. In steps (2) to (5), the substrate temperature is controlled at 80 to 200 °C.

8. The application of the porous transport layer according to claim 1 or the porous transport layer prepared by any one of claims 2-7 as an anode porous transport layer in a proton exchange membrane water electrolyzer.

Citation Information

Patent Citations

  • Process for electroplating platinum coating on titanium felt base material

    CN120465070A

  • Conductive and corrosion-resistant composite coating

    CN121472891A

  • Electrolytic anode and manufacturing method thereof

    CN116288510A

  • Corrosion-resistant and hydrogen embrittlement-resistant composite coating for titanium-based bipolar plate and preparation method thereof

    CN119352062A